2020
DOI: 10.1002/ejoc.202000512
|View full text |Cite
|
Sign up to set email alerts
|

Highly Strained Unsaturated Carbocycles

Abstract: Highly strained unsaturated carbocyclic rings are high‐energy compounds which are attracting increasing interest – not just for their peculiar structural and reactivity features – but also as modern chemical tools for bioorthogonal and in vivo chemistry, especially via inverse‐electron demand Diels–Alder (iEDDA) and strain‐promoted azide‐alkyne cycloaddition (SPAAC) reactions. This mini‐review covers two main classes of compounds: 3 to 10 membered‐ring cycloalkynes and trans‐cycloalkenes, including some exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 138 publications
(148 reference statements)
0
10
0
Order By: Relevance
“…Flash chromatography was performed using silica gel (60 Å, particle size 40-63 μm) purchased from Merck. 1 H NMR and 13 C NMR spectra were recorded on a Bruker AVANCE III 400 NMR spectrometer and calibrated using residual non-deuterated solvent as internal reference. Chemical shifts (δ) are reported in parts per million (ppm) and coupling constants (J) are given in Hertz (Hz).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Flash chromatography was performed using silica gel (60 Å, particle size 40-63 μm) purchased from Merck. 1 H NMR and 13 C NMR spectra were recorded on a Bruker AVANCE III 400 NMR spectrometer and calibrated using residual non-deuterated solvent as internal reference. Chemical shifts (δ) are reported in parts per million (ppm) and coupling constants (J) are given in Hertz (Hz).…”
Section: Methodsmentioning
confidence: 99%
“…See the separate compounds for follow-up purification strategy. [1,2,3]triazol-1-yl)ethoxy)ethoxy)ethoxy)ethan-1ol (3a). Filtration through a pad of silica gel (n-Hex/Ac 2 O 1:1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyclopropane is particularly useful in the development of peptidomimetics, as it can fix its substituents into the trans-or cis-configuration, due its constrain. [41] This behavior is called 'cyclopropylic strain'. [42] In 2013, Mizuno et al reported on the stereoselective synthesis of cyclopropane based tetrapeptide mimics 47-50 (Figure 8), able to stabilize conformations covering β-turn through β-strand, depending on the chirality of the mimic.…”
Section: And 4-membered Ringsmentioning
confidence: 99%